2015
DOI: 10.1007/s11012-015-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Statements on nonlinear dynamics behavior of a pendulum, excited by a crank-shaft-slider mechanism

Abstract: The nonlinear dynamics behavior analyzed, in this paper, consists in a pendulum vertically excited on the support by a crankshaft -slider mechanism. The novelty is the obtainment and analysis of a mathematical model for the pendulum dynamics, under an excitation of a crank-slider, which is based on an extension of the mathematical model of the classical parametric pendulums. Through the modeling, it was verified that the nonlinear dynamics of the pendulum, excited by the crankshaft -slider mechanism approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Compared with the case of single delayed feedback, the quantum dot laser with two delayed feedback proposed in this work will have more rich nonlinear dynamical behaviors by changing the systematical parameter. In reality, the nonlinear dynamics such as periodic and chaotic behaviors that are very significant research subject are also presented and demonstrated based on other interesting physical structures [31][32][33][34][35][36]. Compared with these reported nonlinear dynamical models, the semiconductor quantum dot laser-based periodic and chaotic phenomena will be more useful for the all-optical signal processing in optical communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the case of single delayed feedback, the quantum dot laser with two delayed feedback proposed in this work will have more rich nonlinear dynamical behaviors by changing the systematical parameter. In reality, the nonlinear dynamics such as periodic and chaotic behaviors that are very significant research subject are also presented and demonstrated based on other interesting physical structures [31][32][33][34][35][36]. Compared with these reported nonlinear dynamical models, the semiconductor quantum dot laser-based periodic and chaotic phenomena will be more useful for the all-optical signal processing in optical communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge was to understand whether a sustainable rotational motion could be observed under a sea-like environment excitation, since sea waves could barely resemble a harmonic process. There has been a number of publications related to the rotational potential of a parametrically excited deterministic pendulum, most of which were not concerned with energy harvesting but rather were focused on the deterministic and chaotic response of the pendulum ( [4][5][6][7] and references therein). Rotational potential is defined as a percentage of rotational motion of the pendulum over the overall time and it directly influences the amount of power generated.…”
Section: Introductionmentioning
confidence: 99%
“…A dynamic analysis of a pendulum vertically excited by a crank-shaft-slider mechanism was performed in Avanço et al [4]. In the current literature, the motion of the slider is commonly approached to a harmonic displacement as it was carried out in Krasnopolskaya and Shvets [5], where the chaotic behavior of a nonlinear system was verified.…”
Section: Introductionmentioning
confidence: 99%
“…In the current literature, the motion of the slider is commonly approached to a harmonic displacement as it was carried out in Krasnopolskaya and Shvets [5], where the chaotic behavior of a nonlinear system was verified. The dynamic equation in Avanço et al [4] considered, in the modeling, the complexity of the crank-shaft-slider in the motion on the pivot of support of the pendulum. The geometry of the mechanism was applied like a perturbation in the equation correspondent of the classical parametric pendulum of Leven and Koch [2].…”
Section: Introductionmentioning
confidence: 99%